The acute effects of prior cycling cadence on running performance and kinematics - Gottschall, J. S.; Palmer, B. M. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE To determine if cycling cadence affects subsequent running speed through changes in stride frequency.METHODS Thirteen male triathletes completed three sessions of testing on separate days. During the first session (control condition), the participants completed a 30-min cycling bout of high intensity at their preferred cadence, immediately followed by a 3200-m run at race effort. During the second and third sessions (fast condition and slow condition), the participants repeated the protocol but with a cycling cadence 20% faster or 20% slower than the control condition.RESULTS After cycling at a fast cadence, the 3200-m run time averaged nearly a min faster than after cycling at a slow cadence. Running stride frequency after cycling at a fast cadence was significantly greater than after cycling at a normal or slow cadence. Stride length did not differ between conditions. Joint kinematics at foot strike, mid-stance, toe-off, and mid-swing were not different between conditions.CONCLUSION Increased cycling cadence immediately before running increased stride frequency and, as a result, increased speed.